Digital Leadership and Digital Transformation: Systematic Literature Review - Alawiah, Enok Tuti; Tukiran, Martinus (IJOSMAS, 2024)
This article aims to conduct a systematic review of Digital Leadership and Digital Transformation in Education. The search was conducted for publications in the period 2020-2024 and found 81 articles which were then filtered into 12 articles. The research framework uses PRISMA. The purpose of the study is to identify digital leadership and digital transformation practices in organizations and the field of Education and to find out the development of digital leadership and digital transformation research in organizations and the field of education. This study provides an overview of digital transformation and digital leadership practices in the field of Organizations and Education and the development of research related to digital leadership and digital transformation practices in organizations and the field of Education. The focus of the study is also diverse and reveals many facts about Digital Leadership and Digital Transformation, especially in the field of Organizations and Education.